Portable Air-Cooler System - mat nawi, nur syahirah; hariz aiman; muhammad athari; Nor Baizura Hamid (Multidisciplinary Applied Research and Innovation, 2025)
Malaysia, a tropical country, is seeing economic progress while dealing with growing issues caused by global warming. This study looks into how the need for air conditioning is affected by rising temperatures and how solar energy is being adopted as a sustainable alternative. With Malaysia’s climate, solar power is very promised as a practical way to reduce energy shortages and environmental degradation. The project intends to create an affordable solar-powered portable air cooler, test its viability indoors, and measure the voltage and current output of the solar panel for optimal performance. Tests of voltage and temperature were conducted under various sun circumstances. The data shows a stable temperature decrease over the observed periods (from 10:00 am to 2:20 pm), with decreases of approximately 3.3% to 3.6% from the initial temperature values. This pattern may be influenced by changes in weather conditions or other environmental factors affecting temperatures at that time. Peak temperatures and solar energy output were measured at noon. An average of 6.64V was found during voltage measurements, indicating that the air cooler had enough power. Overall, the solar-powered air cooler shows strong cooling performance in hot weather, confirming its environmental sustainability and operational success. This project demonstrates how Malaysia may use solar energy to lessen its reliance on fossil fuels, reduce its carbon footprint, and combat climate change. This report promotes sustainable approaches to steer Malaysia toward a more environmentally friendly energy landscape while striking a balance between economic growth and environmental stewardship.